Electron Ionization of Adenine. (August 2015) - Rahman, M A; Krishnakumar, E
Synopsis: We present the measurements on absolute total and partial ionization cross sections and fragmentation studies for DNA base Adenine on electron impact using a newly designed experimental setup which uses Time of Flight Mass Spectrometer and the relative flow technique.